The Influence of organizational culture and Work Environment on Employee Performance in Campalagian District Office - Awal Nopriyanto Bahasoan; Rahmat Hasanuddin; Samsuardi Said; Silvia Silvia (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine whether organizational culture and work environment affect employee performance. The location of the research was carried out in the Campalagian sub-district office with 31 employees. Sampling uses a saturated sample in which the entire population is sampled. The data sources are taken from primary and secondary data. Data collection techniques were carried out by distributing questionnaires and observations made by researchers. Qualitative data is processed to become quantitative data results. Some questions addressed to respondents where the answers are quantified by giving a score. The analysis used was the t test using the SPSS version 25.0 windows application. The results showed that (1) Organizational Culture has a positive and significant effect on employee performance. (2) Work environment has no influence and is not significant on employee performance. And the F test analysis shows that Organizational Culture and Work Environment simultaneously have a significant positive effect on employee performance in the Campalagian District office